The quest for therapy in Lower Zaire - Janzen, John M.; Arkinstall, William (University of California Press, 1978)
In this book, Dr. John M. Janzen describes patterns of healing among the BaKongo of Lower Zaire in Africa, who, like many peoples elsewhere, utilize cosmopolitan medicine alongside traditional healing practices. What criteria, he asks, determine the choice of the alternative therapies? And what is their institutional interrelationship? In seeking answers, he analyzes case histories and cultural contexts to explore what social transactions, decisionmaking, illness and therapy classifications, and resource allocations are used in the choice of therapy by the ill, their kinfolk, friends, associates, and specialized practitioners.
free
Keywords: Volksmedizin